Assessment of the Impact of Ceftriaxone on the Functional Profile of Soil Microbiota Using Biolog EcoPlateTM - Livia da Silva Freitas; Rodrigo de Lima Brum; Alícia da Silva Bonifácio; Lisiane Martins Volcão; Flavio Manoel Rodrigues da Silva Júnior; Daniela Fernandes Ramos (Soil Systems, 2023)
Background: Antibiotics are essential to the treatment of diseases, but they have also brought about concerns in terms of their environmental, economic, and health impacts. Antibiotics can be excreted in unchanged form or as metabolites, which can cause toxicity by contaminating different environmental compartments, including soil. Soil is a critical compartment due to the numerous functions it performs and its direct impact on the communities of microorganisms, plants, and animals that make up the soil ecosystem. The functional profile of soil microbiota has emerged as a promising tool to assess soil quality. This study aimed to evaluate the functional profile of soil microbiota and the gut microbiota of earthworms in ceftriaxone-contaminated soil using Biolog EcoPlate. Methods: Soil samples contaminated with varying concentrations of ceftriaxone (0, 1, and 10 mg/kg) were incubated for 14 days in the presence or absence of the earthworm Eisenia andrei. After exposure, the physiological profile of the soil microbiota and the gut microbiota of the earthworms were evaluated using Biolog EcoPlate. Results: No significant differences were observed in the parameters evaluated using different concentrations of the antibiotic. The functional profile of the microbiota in the soil with and without earthworms was found to be similar, but interestingly, it differed from the profile of the intestinal microbiota of the earthworms. Conclusions: The findings of this study indicate that the presence of earthworms did not significantly alter the functional profile of the soil microbiota in ceftriaxone-contaminated soil. Further studies are necessary to investigate the potential impact of ceftriaxone and other antibiotics on soil microbiota and the role of earthworms in this regard.